LEGAL AND REGULATORY BASIS OF ORGANIZING ACTIVITY CENTERS IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (Conferencea, 2023)
There is talk about the establishment of the sixth center with an innovative approach to the five activity centers established in preschool educational organizations.